Raça, classe e gênero e a contribuição de Lélia Gonzalez para o pensamento social - Martins, Mireile Silva (2023)
The intent of this master's dissertation is to introduce the thought and work of Brazilian intellectual Lélia de Almeida Gonzalez (1935-1994) into the field of social thought. With the overall objective of (re)acknowledging and analyzing in a systematic manner the categories of race, class, and gender present in her productions from the years 1979 to 1988, it also seeks to specifically investigate Gonzalez's respective contributions to the construction of thought about racial relations in the late 1970s and the early 1990s, as well as to identify how said intellectual points towards advancements in Brazilian social thought. To achieve this, we work with her thoughts materialized in her essays, interviews, and opinion articles, using exclusively the recent work published as "For an Afro-Latin American and Caribbean Feminism" (2020), organized by Márcia Lima and Flávia Rios. By examining who Lélia Gonzalez opposed and engaged in dialogue with in the construction of a new interpretation of Brazil, we proceed to analyze her work based on the perceptions and concepts developed by Lélia Gonzalez in the late 1970s and 1980s. Rooted in the category of "marginal mass" by José Nun (1978), the intellectual presents her own perspective on the integration of Black people into class society in Brazil, bringing to the forefront of the debate the interplay between the categories of race, class, and gender. These categories were highlighted for analysis because they were identified asfundamental in Gonzalez's thought for understanding the foundational and structural contradictions of the domination/exploitation of Black individuals, especially Black women, in Brazil. The legacy and conceptual advancement of these categories in Lélia Gonzalez's work are explored, drawing from the notions of "mulata," domestic worker, and "mãe-preta" (Black mother) present in her texts. This exploration reveals her contribution to the studies of racial relations in Brazil and to social thought, uncovering an explicit understanding of intersectionality (Crenshaw, 1989) even before the term was coined, thus illustrating Lélia Gonzalez as a pioneer in this discussion.